Pengembangan Komik Mitigasi Berbasis Potensi Bencana Lokal yang Terintegrasi dalam Pembelajaran Fisika di Sulawesi Tengah - Fittri Yani; Unggul Wahyono (Department of Physics Education, Universitas Mataram, 2020)
This study aims to produce appropriate learning media in supporting the implementation of learning about disaster mitigation. The type of research used is Research and Development (R&D) and uses the 4D development model namely Define, Design, Develop and Disseminate. After becoming a product, it is then validated by material experts and media experts. The results of the material expert validation obtained an average score of 3,13 in the